INFORMALIDAD LABORAL EN LA REGIÓN PIURA, 2017: UN ANÁLISIS DE LOS DETERMINANTES - Timaná Álvarez, Marcos (2021)
In this study the determinants of labor informality in the Piura 2017 region were analyzed; in order to infer public policy guidelines that allow people to enter the formal labor market. The structuralist approach gives priority in explaining labor informality to the scarce development of the modern sector of the economy; while the institutionalist approach explains that the presence of in-formal activities is due to the legal barriers that exist in the modern sector of the economy. For the analysis of the determinants of labor informality, a logit econometric model was estimated. The information was obtained from the ENAHO (2017) database for the Piura region. Among the main results, it was found that age, sex, head of household, area of residence, size of the company and the different educational levels of the person, had an inverse influence.